Smart Packaging Berbasis Limbah Agro sebagai Strategi Ekosentris dalam Mengurangi Dampak Lingkungan Industri Pangan - Ayu, Hanifah; Muhammad, Sarjan (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2026)
The food industry's dependence on conventional plastics has created an environmental crisis, impacting CO2 emissions, plastic waste accumulation, and microplastic pollution. On the other hand, the agro-industrial sector produces millions of tons of abundant biomass waste rich in biopolymers and bioactive compounds, but most of it is still managed through open burning or dumped in landfills. This study aims to examine the potential of agro waste based smart packaging as an eco centric strategy to reduce the ecological impact of the food industry. A qualitative descriptive method approach is used through a review of technical and philosophical literature on ecocentrism. Agro waste based smart packaging can be processed into bioplastics and biodegradable smart packaging that effectively reduce food waste and food loss. Although its initial production is more energy-intensive, the long-term benefits reduce the carbon footprint and total ecological burden. This agro-waste-based smart packaging reflects an eco-centric strategy and simultaneously demands systemic policies and innovations to strengthen food security and support SDGs 12 and 13. The implementation of smart packaging based on agro-waste can act as a strategic instrument to overcome the plastic crisis, reduce agricultural waste and strengthen food security, while also demanding integrated policies, investments and innovations that strictly refer to the principles of ecocentrism.